Metal–Organic‐Framework‐Based Catalysts for Photoreduction of CO2 - Li, Rui; Zhang, Wang; Zhou, Kun (Advanced materials (Weinheim), 2018)
Photoreduction of CO2 into reusable carbon forms is considered as a promising approach to address the crisis of energy from fossil fuels and reduce excessive CO2 emission. Recently, metal–organic frameworks (MOFs) have attracted much attention as CO2 photoreduction‐related catalysts, owing to their unique electronic band structures, excellent CO2 adsorption capacities, and tailorable light‐absorption abilities. Recent advances on the design, synthesis, and CO2 reduction applications of MOF‐based photocatalysts are discussed here, beginning with the introduction of the characteristics of high‐efficiency photocatalysts and structural advantages of MOFs. The roles of MOFs in CO2 photoreduction systems as photocatalysts, photocatalytic hosts, and cocatalysts are analyzed. Detailed discussions focus on two constituents of pure MOFs (metal clusters such as Ti–O, Zr–O, and Fe–O clusters and functional organic linkers such as amino‐modified, photosensitizer‐functionalized, and electron‐rich conjugated linkers) and three types of MOF‐based composites (metal–MOF, semiconductor–MOF, and photosensitizer–MOF composites). The constituents, CO2 adsorption capacities, absorption edges, and photocatalytic activities of these photocatalysts are highlighted to provide fundamental guidance to rational design of efficient MOF‐based photocatalyst materials for CO2 reduction. A perspective of future research directions, critical challenges to be met, and potential solutions in this research field concludes the discussion. Photocatalyst materials based on metal–organic frameworks (MOFs) have great potential for carbon dioxide (CO2) reduction due to their tailorable light‐absorption ability, unique pore texture, and excellent CO2 adsorption capacity. A comprehensive review of recent advances in the design, synthesis, and CO2 photoreduction applications of MOF‐based photocatalysts is presented to offer valuable insights toward the exploitation of new‐generation photocatalyst materials.